IMPLEMENTASI PENDIDIKAN MULTIKULTURAL MELALUI MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENCEGAH BERKEMBANGNYA PAHAM RADIKALISME DI KALANGAN PESERTA DIDIK - Dadang Mulyana; Cahyono Cahyono; Lili Sukarliana; Eri Munggaran (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2021)
This research was conducted by researchers to find out how important the implementation of multicultural education is in preventing the development of radicalism among students through Pancasila and Citizenship Education subjects. As a result of the development of radicalism, there is a lack of tolerance for others which results in the loss of a sense of unity and integrity among students. In this study, the researcher used a case study method, using a qualitative approach. The data collection used is through interviews and literature studies. The population in this study were all students in one of the Pasundan Vocational Schools in Bandung. The sample of this research is representatives of class XI students as many as 11 people. Through interviews with Pancasila and Citizenship Education teachers and student representatives. The results show that the learning process of Pancasila and Citizenship Education by implementing multicultural education makes learning activities more active so that they can instill diversity or multicultural values ​​and prevent students from the impact of radicalism such as acts of intolerance among students. So we can conclude that the implementation of multicultural education has an impact on preventing the development of radicalism among students through Pancasila and citizenship education subjects.